PENGARUH Ph, KADAR XILOSA DAN KADAR GLUKOSA TERHADAP PRODUKSI XYLITOL OLEH Candida shehatae WAY 08 [The Influence of Intial Xylose and Glucose Consentration on Xylitol production by Candida shehatae WAY 08] - Wisnu Adi Yulianto (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2001)
The objectiviea of this research were to determine the optimum culture conditions of initial pH, xylose and glucose concentration for xylitol production by Candida shehatae WAY 08. The initial pH was altered whitin the range of 4-7, the xylose concentration from 5020%, and the glucose (cosubstrate) from 0-4%. The fermentation was performed at 30°C in 500 ml erlenmeyer flaks placed in a shaker incubator at 250 rpm for 7d. biomas concentration war determined by oven method. Xylose, glucose and xylitol concentrations were determined by HPCL.the result incated that the highest xylitol volumetric productivity of Candida shehatae WAY 08 was 0,314 g/I/h at the initial pH of 5 in medium containing 150 g/I xylose. Addition of glucose into media inhibited the xylitol production, but in creased the xylitol yield.